Antibacterial Prophylaxis of Infectious Complications in a Pediatric Surgeon’s Practice - E. Yu. Diakonova; N. V. Loban; I. V. Poddubnyi; A. A. Bekin; A. A. Gusev; T. A. Prudnikova (Педиатрическая фармакология)
The evolution of postoperative wound infections complicates the postoperative period, prolongs the hospitalization and increases the cost of treatment. The most effective way to prevent the development of infection complications in the world is antibacterial prophylaxis. In surgery, that means the injection of an antibiotic immediately before and during twenty-four hours after the surgery. The article presents a characteristic of risk factors for postoperative complications, indications and the basic principles of antibiotic prophylaxis, and recommendations for the selection of antimicrobials, depending on the particular clinical case.